TRANSFORMASI PERBANKAN KONVENSIONAL OLEH FINTECH DALAM EKONOMI BERBASIS PLATFORM DIGITAL - halide, nabilaputrimaharani; Fani, Rezki (IAIN Parepare, 2025)
This study investigates the transformative impact of financial technology (fintech) on the conventional banking sector within the framework of a platform-based digital economy. Employing a Systematic Literature Review (SLR) methodology, the research systematically analyzes 30 peer-reviewed journal articles published between 2015 and 2023. The objective is to explore the evolving dynamics between banks and fintech firms, focusing on patterns of strategic collaboration, institutional adaptation, and technological integration. The findings reveal that the relationship between traditional banks and fintech has shifted from one of disruption to symbiotic cooperation, wherein fintech contributes agility and innovation, while banks offer infrastructure, regulatory legitimacy, and consumer trust. This transformation facilitates the development of more efficient, inclusive, and sustainable financial services. The study underscores the critical role of adaptive regulatory frameworks, enhanced digital literacy, and the incorporation of Islamic digital financial tools in supporting this transformation, particularly in the context of Islamic banking. It recommends policy strategies such as open banking architecture and enabling regulation models to foster innovation while ensuring systemic stability and inclusivity.